The handbook of corporate earnings analysis : company performance and stock market valuation - Bruce, Brian R.; Epstein, Charles B. (Chicago, Ill. : Probus Pub. Co., 1994)
The origins for this book stemmed from some of the major changes which have swept over the investment analysis business: the introduction of programs to objectively measure analyst revisions via electronic media; and most importantly, the tremendous growth in the amount of investment analyst research being produced on a daily basis.
Spine title: Corporate earnings analysis.
Includes bibliographical references and index.
osc 14/01/2019
Loans
Keywords: Corporate profits--Forecasting; Stock price forecasting; Investment analysis; United States